Design Novel Fuzzy Logic Controller of IPMSM for Electric Vehicles - Huangyuan, Wu; Shuanghong, Wang; Keran, Shao; Sun, Jianbo (Elektronika ir Elektrotechnika, 2014)
This paper presents a novel fuzzy logic controller (FLC) for an interior permanent magnet synchronous motor (IPMSM) in electric vehicles (EV). As an IPMSM used for electric vehicles, d- and q-axis inductances are varied in wide range. Thus, based on inductances variation, the inductances are analysed as a function of both current magnitude and phase. Then, a novel fuzzy logic control algorithm is proposed that that uses the parameters variation of the inductances is proposed. The algorithm adjusts the reference current of the drive system according to the speed and torque statues. A digital signal processor (DSP) chip TMS28335 is used to implement a complete drive system for a 50kW IPMSM prototype motor. Experimental results have been carried out in order to prove the effectiveness of the new FLC. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.5870